Implementing Samsung Digital Technology in Pesantren Learning: A Qualitative Case Study of Adaptive Integration at Pondok Thursina - Assiddiqi, Jimly; Faris Khoirul Anam; Muhammad Fadhil Hadziq (NAJAHA, 2026)
Digital transformation in education presents Indonesian pesantren, that is, Islamic boarding schools rooted in face to face transmission of religious knowledge through sorogan, bandongan, and halaqah, with both opportunity and tension. This qualitative case study examines how Pondok Thursina, a modern pesantren in East Java, integrates Samsung Digital Classroom technology while preserving its religious and communal identity. A single site embedded case study was conducted over five months (January to May 2026), drawing on twenty four nonparticipant classroom observations across general and religious subjects, semistructured interviews with eighteen informants (two kiai, eight ustadz, eight santri), and analysis of institutional documents and student digital artifacts. Data were analysed thematically using Miles, Huberman, and Saldaña’s interactive model, with trustworthiness ensured through source and method triangulation, member checking, peer debriefing, and a complete audit trail. Findings reveal four interrelated themes: (1) layered remediation that augments rather than replaces classical pedagogy; (2) emergent Digital Pedagogical Content Knowledge for Pesantren (DPCKP) cultivated through peer micromentoring; (3) cultural and spiritual content filtering through musyawarah and adab norms; and (4) structural tensions involving infrastructure, screen time governance, and asymmetric digital literacy among santri. The study advances the Pesantren Digital Integration Model (PDIM), extending Mishra and Koehler’s TPACK with two pesantren specific axes: spiritual and cultural alignment, and communal and spatial pedagogy. Findings inform Islamic education policy, EdTech vendors operating in faith based settings, and pesantren leaders pursuing digitisation without detraditionalisation.